FISCAL POLICY TRANSFORMATION THROUGH BUDGET EFFICIENCY: A PUBLIC ADMINISTRATION AND CONSTITUTIONAL LAW PERSPECTIVE - Rangkuti, Afifa (Hukum tata Negara/Siyasah, 2025)
This study aims to understand the meaning and role of budget efficiency in promoting the development of governance, especially in the context of public financial governance reform. The background of this study rests on the need for transparency and accountability in local financial management in the era of autonomy, given the complexity of the relationship between central and local governments and the challenges in the effective use of the Regional Budget (APBD). The research method used is descriptive qualitative with a literature approach and theoretical analysis of the concept of budget efficiency, as well as reflection on budget efficiency policies implemented by President Prabowo's administration in 2025. The results show that budget efficiency is not simply an austerity measure, but rather a systemic strategy to restructure the bureaucracy, reduce waste, and shift state spending to productive sectors through a performance-based approach. The novelty of this research lies in presenting an analysis of budget efficiency within the framework of contemporary constitutional law and public administration, and linking it to the dynamics of institutional reform, digitized procurement systems, and strengthening performance-based fiscal autonomy. This study recommends that budget efficiency should be implemented as part of a smart governance strategy that emphasizes fairness, transparency, and public participation in the national development process.Keywords: Budget Efficiency, Governance, APBD, Bureaucratic Reform, Good Governance